EFEKTIVITAS PEMBIAYAAN KEPEMILIKAN RUMAH MELALUI KREDIT PERUMAHAN RAKYAT (KPR) DI KALUKUBULA RESIDENCE SIGI (STUDI PADA KONSUMEN DEVELOPER PT APININDO CIPTA SEJATI) - Suriyadewi, Suriyadewi; Usman, Ernawaty; Kahar, Abdul; Yuniar, Latifah Sukmawati (Politeknik Negeri Ambon, 2025)
Introduction: The purpose of this study is to assess how well the subsidized Sharia Home Ownership Credit (KPR) financing was distributed at BTN Green Kalukubula Residence in Sigi Regency. Methods: Descriptive qualitative methodology is employed, and data is directly gathered through in-depth interviews and the distribution of questionnaires to 47 informants. As a supplementary analysis, the Artificial Neural Network (ANN) method is also employed. Results: The study's findings demonstrate that the Subsidized Sharia Mortgage financing scheme is seen to be quite successful in assisting those with low incomes in becoming homeowners. The amount of financing margin, the implementation of late installment penalties, and information openness are some of the remaining challenges that must be taken into account. Therefore, in order to boost potential customers' trust, banks and developers are advised to promote information openness. Conclusion and suggestion: This study's drawback is that it was challenging to contact certain respondents since many of them were at work or not at home, which made the data gathering method less than ideal.